1999
DOI: 10.1007/s004250050642
|View full text |Cite
|
Sign up to set email alerts
|

Rapid stalk elongation in tulip ( Tulipa gesneriana L. cv. Apeldoorn) and the combined action of cold-induced invertase and the water-channel protein γTIP

Abstract: Many bulbous plants need a low-temperature treatment for flowering. Cold, for example, affects the elongation of the stalk, thereby influencing the quality of the cut flower. How the elongation of the stalk is promoted by cold and which physiological and biochemical mechanisms are involved have remained obscure. As invertase has been shown to be involved in the cold-induced elongation of the flower stalks of tulips (Lambrechts et al., 1994, Plant Physiol 104: 515-520), we further characterized this enzyme by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 50 publications
2
31
0
1
Order By: Relevance
“…S2). These are VIN hallmarks (Vitale and Chrispeels, 1992;Balk and de Boer, 1999;Sturm, 1999) that are absent from the two CWINs, OsCWI1 and NtCWIN1, included in the comparison. Furthermore, GhVIN1 displayed five distinctive amino acids (indicated by arrows in Supplemental Fig.…”
Section: Cloning Of Ghvin1 That Localizes To the Vacuolementioning
confidence: 99%
“…S2). These are VIN hallmarks (Vitale and Chrispeels, 1992;Balk and de Boer, 1999;Sturm, 1999) that are absent from the two CWINs, OsCWI1 and NtCWIN1, included in the comparison. Furthermore, GhVIN1 displayed five distinctive amino acids (indicated by arrows in Supplemental Fig.…”
Section: Cloning Of Ghvin1 That Localizes To the Vacuolementioning
confidence: 99%
“…Phylogenetic analyses were conducted using MEGA version 4 (Tamura et al, 2007) and the neighbor-joining method. The accession numbers of the sequences used to construct the phylogenetic tree are as follows: AtSUS1-AtSUS6 from Arabidopsis, At5g20830, At5g49190, At4g02280, At3g43190, At5g-37180, and At1g73370, respectively (Baud et al, 2004); Ag-SUS from Alnus glutinosa, X92378 (van Ghelue et al, 1996); BoSUS1-BoSUS4 from Bambusa oldhamii, AF412036, AF-412038, AF412037, and AF412039, respectively; BvSBSS1 and BvSBSS2 from sugar beet, AY457173 and EF660856, respectively (Hesse and Willmitzer, 1996;Klotz and Haagenson, 2008); ClSUS from Citrullus lanatus, AB018561; Cpss1 and Cpss2 from Craterostigma plantagineum, AJ131999 and AJ132000, respectively (Kleines et al, 1999); CrSUS from Chenopodium rubrum, X82504 (Godt et al, 1995); CitSUS1 and CitSUSA from citrus, AB022092 and AB022091 (Komatsu et al, 2002); DcSUS1 and DcSUS2 from carrot, X75332 and Y16091 (Sebkova et al, 1995;; GhSUS from Gossypium hirsutum, U73588; GmSUS from soybean, AF030231; HvSUS1 and HvSUS2 from barley, X65871 and X69931 (Sánchez de la Hoz et al, 1992); LeSUS1 and Le-SUS2 from tomato, L19762 and AJ011319 (Chengappa et al, 1999;Wang et al, 1993); MsSUS from Medicago sativa, AF049487; MtSUS1 from Medicago truncatula, AJ131943 (Hohnjec et al, 1999); MySUS from the tropical epiphytic CAM orchid Mokara Yellow, AF530568 (Li et al, 2004); OgSUS from the tropical epiphytic orchid Oncidium goldiana, AF530567; OsSUS1-OsSUS7 from rice, LOC_Os03g28330, LOC_Os06g 09450, LOC_Os07g42490, LOC_Os03g22120, LOC_Os04g 24430, LOC_Os02g58480, and LOC_Os04g17650, respectively (Hirose et al, 2008;Huang et al, 1996;Wang et al, 1992); PdSUS1 and PdSUS2 from Potamogeton distinctus, AB193515 and AB193516; PtSUS from Populus tremuloides, AY341026; PvSS from bean, AF315375 (Silvente et al, 2003); PsSUS1-PsSUS3 from pea, AJ012080, AJ001071, and AJ311496, respectively (Barratt et al, 2001;Craig et al, 1999); SoSusy2 from Saccharum officinarum, AY118266; StSUS2-StSUS4 from potato, AY205302, U24088, and U24087, respectively (Fu and Park, 1995;Salanoubat and Belliard, 1987); TaSUS1 and TaSUS2 from Triticum aestivum, AJ001117 and AJ000153; TgSUS1 and TgSUS2 from tulip, X96938 and X96939 (Balk and de Boer, 1999); VfSUS from fava bean, X69773; Vrvss1 from mung bean, D10266 …”
Section: Sequence Comparisons and Phylogenetic Analysismentioning
confidence: 99%
“…A role for vacuolar invertase has been implicated in a broad range of expanding young sinks such as elongating silks , tulip (Tulipa spp.) stalks (Balk and de Boer, 1999), tobacco (Nicotiana tabacum) leaves (Hoffmann et al, 1997), carnation (Dianthus caryophyllus) petals (Woodson and Wang, 1987), and carrot (Daucus carota) tap roots . Zinselmeier et al (1999) found that drought stress decreased ovary water potential and turgor unless plant stems were infused with Suc.…”
Section: Role Of Vacuolar Invertase In Young Ovariesmentioning
confidence: 99%